Pre-Trial Resolution of Administrative Disputes in Lithuania: Substantive Aspects of Special Legal Provisions - Paškevičienė, Laura (Teisė, 2018)
[only abstract and summary in English; full article and abstract in Lithuanian] In this article, the author analyzes special legal provisions regulating legal administrative out-of-court dispute resolution in the main specific spheres of public administration, seeking to estimate the legal clarity of these provisions and the level of their harmonization with general legal provisions of the pre-trial administrative dispute resolution. The author is trying to investigate the character of special legal regulation particularly in the matter of its position in the hierarchy of law and of different regulative models of placing a dispute to different subjects in binding or facultative stages in order to evaluate both quantitatively and qualitatively the clarity of special regulation with regard to the possibility of ascription of the specific dispute resolution type to the pre-trial administrative process or administrative procedures. Summary In Lithuanian legal system, administrative out-of-court dispute resolution is vastly regulated by the provisions of special legislation in separate fields of administrative law. Commonly here the administrative dispute resolution is legally assigned to the administrative bodies performing public administration. In previous article having examined that, in the provisions of general laws, the legal category of the pre-trial administrative dispute resolution is described especially concisely, providing it should be established by the law, but lacks further qualitative criteria to the whole system and relies on the lawmaking in those specific public administration spheres, now the author continuously seeks to investigate special legal provisions regulating the legal administrative out-of-court dispute resolution. This research is focused on estimating the legal clarity of these provisions and the level of their harmonization with general legal provisions of the pre-trial administrative dispute resolution, and the ascription of the specific dispute resolution type to the latter resolution process, or administrative procedures. Therefore, the author analyzes the character of the specific regulation particularly in the matter of their position in the hierarchy of law and different regulative models of the dispute resolution, according to the clarity of the reference to common provisions, the dispute resolving subjects and the binding or facultative stages of dispute resolution. The analysis is based on quantitative and qualitative evaluation of the special regulation. The author comes to conclusions that, in various fields of administrative regulation, the specific legal provisions of the administrative dispute resolution are established in sub-statutory legal regulation, which under the principle of legality in all cases should not contradict the statute provisions, inter alia, the statutory provisions, which require that the pre-trial dispute resolution should be established by the law. The vast delegation of legislation in this sphere can potentially and really impose problems of the clarity and certainty of the legal regulation of the pre-trial administrative dispute resolution. The reduction of the delegated legislation, and instead, increasing and expanding the regulation of the pre-trial administrative dispute resolution by general laws would be eligible in order to achieve overall legal clarity and consolidate the legal regulation of the pre-trial administrative dispute resolution. Also, it is concluded that the less part of the researched special legal regulation refers to the general regulation, directly pointing to the category of the pre-trial administrative dispute resolution as described in the Law on Administrative Proceedings or redirecting to the provisions of the latter, or the Laws on Administrative Dispute Commissions and on Public Administration. In most cases, the special provisions are self-contained in assigning the administrative dispute regulation to particular administrative authorities. Hence, the regulative approach in this dominating part of special legislation can be described as the dissociation from the general categories of the pre-trial dispute resolution or administrative procedures. The modeling of the dispute resolution types described by the special legislation showed different combinations of dispute resolution levels by the internal administrative control, general pre-trial in administrative dispute commissions and in court. Most of this special regulation in practice requires systemic legal interpretation because it does not give clear provisions about the nature of the proceedings of the dispute resolution. As the pre-trial administrative dispute resolution is not sufficiently regulated in positive law, the main role in clarifying its general and special provisions lies in court jurisprudence.